150k views
23 votes
Y= -3x + 1 and y= x - 3

User Dtortola
by
4.9k points

1 Answer

7 votes

Answer:

x= 1

y= -2

Explanation:

equation (1): y= -3x+1

equation (2): y=x-3

solve the system of equations by substitution:

step1: sub ( x-3 ) for y in equation 1:

y = -3x+1

x-3 = -3x+1

step2: simplify the equation to get x:

(add 3 for both sides)

x = -3x+4

(add 3x for both sides)

4x = 4

(divide 4 from both sides)

x = 1

step3: sub the value of x (x=1) in equation 2:

y = x-3

y = 1-3

step4: solve the equation to get y:

y = -2

User Dumamilk
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.